2022
DOI: 10.1007/s40119-022-00263-9
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic and Cardiovascular Events and Treatment Patterns Among Patients Hospitalized with COVID-19 in Japan: An Analysis of a Nationwide Medical Claims Database

Abstract: Introduction Limited data are available regarding the prevalence of thrombotic/cardiovascular disease and treatment patterns for patients with coronavirus disease 2019 (COVID-19) in Japan. In this study we describe patients hospitalized for COVID-19 in Japan. Methods This retrospective database study analyzed the Japan Medical Data Vision database (416 acute care hospitals) for patients hospitalized for COVID-19 during the identification period from 1 January 1 to 30 Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This may have been because some ACS patients were worried about contracting COVID-19, and some patients with mild symptoms may have chosen to take medicine at home instead of going to the hospital. COVID-19 directly affects the development of thrombotic coronary obstruction and can lead to myocardial infarction through several mechanisms, such as inducing an inflammatory storm, a hypercoagulable state, or thrombosis, or through viral infiltration of myocardial cells or other immunologic mechanisms [ 13 , 14 , 15 , 16 , 17 ]. Previous clinical studies have demonstrated that ACS morbidity and mortality have significantly increased during the COVID-19 pandemic [ 5 , 6 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may have been because some ACS patients were worried about contracting COVID-19, and some patients with mild symptoms may have chosen to take medicine at home instead of going to the hospital. COVID-19 directly affects the development of thrombotic coronary obstruction and can lead to myocardial infarction through several mechanisms, such as inducing an inflammatory storm, a hypercoagulable state, or thrombosis, or through viral infiltration of myocardial cells or other immunologic mechanisms [ 13 , 14 , 15 , 16 , 17 ]. Previous clinical studies have demonstrated that ACS morbidity and mortality have significantly increased during the COVID-19 pandemic [ 5 , 6 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%